Evaluation of the effects of co-culture system of human dental pulp stem cells and epithelial cells on odonto/osteogenic differentiation capacity - Sang-Yun Lee; Seong-Ju Oh; Rubel Miah; Yong-Ho Choe; Sung-Lim Lee; Yeon Woo Jeong; Young-Bum Son (The Korean Society of Animal Reproduction and Biotechnology, 2024)
Background: In healthy dentin conditions, odontoblasts have an important role such as protection from invasion of pathogens. In mammalian teeth, progenitors such as mesenchymal stem cells (MSCs) can migrate and differentiate into odontoblast-like cells, leading to the formation of reparative dentin. For differentiation using stem cells, it is crucial to provide conditions similar to the complex and intricate in vivo environment. The purpose of this study was to evaluate the potential of differentiation into odonto/osteoblasts, and compare co-culture with/without epithelial cells. Methods: MSCs and epithelial cells were successfully isolated from dental tissues. We investigated the influences of epithelial cells on the differentiation process of dental pulp stem cells into odonto/osteoblasts using co-culture systems. The differentiation potential with/without epithelial cells was analyzed for the expression of specific markers and calcium contents. Results: Differentiated odonto/osteoblast derived from dental pulp tissue-derived mesenchymal stem cells with/without epithelial cells were evaluated by qRT-PCR, immunostaining, calcium content, and ALP staining. The expression of odonto/osteoblast-specific markers, calcium content, and ALP staining intensity were significantly increased in differentiated cells. Moreover, the odonto/osteogenic differentiation capacity with epithelial cells co-culture was significantly higher than without epithelial cells co-culture. Conclusions: These results suggest that odonto/osteogenic differentiation co-cultured with epithelial cells has a more efficient application.